CXCL12 secreted by pancreatic stellate cells accelerates gemcitabine resistance of pancreatic cancer by enhancing glycolytic reprogramming - Xiangyu Lu; Yilei Wu; Rui Cao; Xiaojiong Yu; Jun Gong (Animal Cells and Systems, 2022)
Pancreatic stellate cells (PSCs) are the primary cell components of pancreatic cancer (PC) and are involved in tumor growth, metastasis and resistance. However, the role and the mechanism of PSCs in gemcitabine (GEM) resistance to PC still need more investigation. We found that CXCL12 mRNA and secreted CXCL12 protein were higher in PSCs after GEM treatment. The conditioned medium (CM) from GEM-treated PSCs reduced the GEM sensitivity of PC cells. Blocking of CXCL12 in CM by anti-CXCL12 antibody partly restored the GEM sensitivity of PC cells. Blocking of CXCL12 decreased glucose consumption, lactate production, ECAR, and glycolysis-related gene expression in PC cells. The PI3K/AKT/mTOR pathway was activated by the binding of CXCL12 and CXCR4. Moreover, CXCR4 mRNA and protein expressions in PC cells were increased after GEM treatment. Our results indicated the cross-talk between PSCs and PC cells during GEM chemotherapy. CXCL12 secreted by PSCs reduces GEM sensitivity of PC cells by binding to CXCR4 and activating PI3K/AKT/mTOR-glycolysis pathway in PC. Our findings would lay the foundation for solving GEM resistance in PC.